Effect of Preoperative Urodynamic Study on Urinary Outcomes after Transobturator Sling - Pedro Rincon Cintra da Cruz; Aderivaldo Cabral Dias Filho; Gabriel Nardi Furtado; Rhaniellen Silva Ferreira; Ceres Nunes Resende (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To evaluate whether performing preoperative urodynamic study influences postoperative urinary symptoms of women with stress urinary incontinence that underwent transobturator sling. Methods Retrospective analysis of patients treated for stress urinary incontinence by transobturator sling from August 2011 to October 2018. Predictor variables included preoperative urodynamic study, age, incontinence severity, body mass index, preoperative storage symptoms and previous anti-urinary incontinence procedure. Outcome variables were postoperative subjective continence status, storage symptoms and complications. Logistic regression after propensity score was employed to compare outcomes between patients who underwent or not pre-operative urodynamic study. Results The present study included 88 patients with an average follow-up of 269 days. Most patients (n = 52; 59.1%) described storage symptoms other than stress urinary incontinence, and 38 patients (43.2%) underwent preoperative urodynamic studies. Logistic regression after propensity score did not reveal an association between urinary continence outcomes and performance of preoperative urodynamic study (odds ratio 0.57; confidence interval [CI]: 0.11-2.49). Among women that did not undergo urodynamic study, there was a subjective improvement in urinary incontinence in 92% of the cases versus 87% in those that underwent urodynamic study (p = 0.461). Furthermore, postoperative storage symptoms were similar between women who did not undergo urodynamic study and those who underwent urodynamic study, 13.2% versus 18.4%, respectively (p = 0.753). Conclusion Preoperative urodynamic study had no impact on urinary incontinence cure outcomes as well as on urinary storage symptoms after the transobturator sling in women with stress urinary incontinence.